[2.2.1]-Bicyclic sultams as potent androgen receptor antagonists. Issue 23 (1st December 2016) - Shan, Weifang; Balog, Aaron; Nation, Andrew; Zhu, Xiao; Chen, Jing; Cvijic, Mary Ellen; Geng, Jieping; Rizzo, Cheryl A.; Spires, Thomas; Attar, Ricardo M.; Obermeier, Mary; Traeger, Sarah; et al.
Graphical abstract: This letter describes the discovery, synthesis, SAR, and biological activity of [2.2.1]-bicyclic sultams as potent antagonists of the androgen receptor. Optimization of the series led to the identification of compound25, which displayed robust pharmacodynamic effects in rats after oral dosing. Abstract: This letter describes the discovery, synthesis, SAR, and biological activity of [2.2.1]-bicyclic sultams as potent antagonists of the androgen receptor. Optimization of the series led to the identification of compound25, which displayed robust pharmacodynamic effects in rats after oral dosing.